Assembly and dynamics of an anastral:astral spindle: the meiosis II spindle of Drosophila oocytes. - Endow, S.A.; Komma, D.J. (Journal of Cell Science, 1998)
The meiosis II spindle of Drosophila oocytes is distinctive in structure, consisting of two tandem spindles with anastral distal poles and an aster-associated spindle pole body between the central poles. Assembly of the anastral:astral meiosis II spindle occurs by reorganization of the meiosis I spindle, without breakdown of the meiosis I spindle. The unusual disk- or ring-shaped central spindle pole body forms de novo in the center of the elongated meiosis I spindle, followed by formation of the central spindle poles. gamma-Tubulin transiently localizes to the central spindle pole body, implying that the body acts as a microtubule nucleating center for assembly of the central poles. Localization of gamma-tubulin to the meiosis II spindle is dependent on the microtubule motor protein, Nonclaret disjunctional (Ncd). Absence of Ncd results in loss of gamma-tubulin localization to the spindle and destabilization of microtubules in the central region of the spindle. Assembly of the anastral:astral meiosis II spindle probably involves rapid reassortment of microtubule plus and minus ends in the center of the meiosis I spindle - this can be accounted for by a model that also accounts for the loss of gamma-tubulin localization to the spindle and destabilization of microtubules in the absence of Ncd.